2019
DOI: 10.3390/mca24040099
|View full text |Cite
|
Sign up to set email alerts
|

Factors for Marketing Innovation in Portuguese Firms CIS 2014

Abstract: Globalization, radical and frequent changes as well as the increasing importance of applying knowledge through the efficient implementation of innovation is critical under the current circumstances. Innovation has been the source of businesses competitive advantage, but it is not restricted to technological innovations, and thus marketing innovation also plays a central role. This is a significant topic in the marketing field and not yet deeply analysed in academic research. The main objective of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Recent research has shown that there is a strong connection between internationalization and innovation (e.g. Monteiro, Correia, et al, 2019). The literature shows, for example, that Latin American multinational firms are more likely to innovate than domestic ones, due to the increased access to new markets, new technologies, and new customers that internationalization provides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that there is a strong connection between internationalization and innovation (e.g. Monteiro, Correia, et al, 2019). The literature shows, for example, that Latin American multinational firms are more likely to innovate than domestic ones, due to the increased access to new markets, new technologies, and new customers that internationalization provides.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the ever-changing socio-cultural conditions in the world and the tremendous growth in the number of women-owned businesses, there is a growing interest in research on women entrepreneurship (Brush, 1992;Jafari-Sadeghi et al, 2021;Monteiro, Correia, et al, 2019;Rosenbaum, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Marketing innovation is a tool that helps managers use their resources effectively and create a competitive advantage. (Bilan et al, 2020;Monteiro et al, 2019). Marketing innovation can improve reputation or company image, increase profits through increased customer satisfaction, identify processes and develop new ideas to gain a competitive advantage (Scott, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Outra lacuna apresentada compreende no trabalho pensando em outros stakeholders, como fornecedores e concorrentes, compreendendo as diferenças sociais, culturais e econômicas entre os clientes e também os efeitos dos ativos de marketing sustentáveis sobre eles(Hussain et al, 2020).• A observação do relacionamento entre os departamentos de marketing e P&D, gastos com inovações e suas informações de profundidade e escopo(Joueid & Coenders, 2018) e a verificação da mudança comportamental das empresas no que diz respeito à importância do marketing e da própria inovação(Monteiro, Correia & Braga, 2019), são fatores a ser considerados.As pautas futuras incorporam principalmente no setor de manufatura mais investimentos em quatro tipos de inovação (produto, processo, marketing e organizacional) associado à performance de marketing(Haudi, Wijoyo & Cahyono, 2020;Kipkosgei & Paul, 2019;Ganzer, Chais & Olea, 2017), fornecendo alguma forma de treinamento que destacaria os méritos de inovação nas empresas e como essas inovações se traduzem em marketing. O impacto da inovação em marketing sobre o desenvolvimento e estabelecimento de outras indústrias do âmbito internacional, além da proposta do setor automotivo, amplia a visão realista das inovações na indústria(Abdolvand & Pakari, 2017), com pesquisas que apresentem um continuum em vez de continuidade.…”
unclassified